(untitled) (Environment & Health, 2017)
Objective: We performed the ecological-and-hygienic assessment of the state of water supply, including a quality of drinking water for the urban population of the Rivne oblast, by sanitary-and-chemical and sanitary-and-microbiological indicators, tendencies in dynamics. Materials and methods: In our study we used the materials of the WHO, the State Sanitary-and-Epidemiological Service of Ukraine, as well as the results of the laboratory investigations of drinking water samples from the sources and the networks of centralized water pipelines in the settlements of the Rivne oblast. Results: A systematization and analysis of the data of drinking water quality, carried separately from the sources and the network of centralized water- pipes to the urban population in the regions of the Rivne oblast in the period from 1999 to 2015, was performed in the study. There was a disparity of sanitary norms and rules in the operation of centralized water pipes mainly due to the non-observance of sanitary protection zones of water sources, lack of necessary complex of treatment facilities and sewage treatment plants. A percentage of the non-conformance of drinking water samples from the sources and the network of centralized water supply by sanitary and chemical indicators increased 1.6 times in dynamics over the period under study. At the same time, a discrepancy between drinking water samples and microbiological indicators increased (almost 4-fold) last years.